Implementing Defense-in-Depth Framework on Orange Pi NAS Using Host-Based Security and ZFS - Hady, Muhammad Fatih; Pratama, Hafiyyan Putra (Politeknik Negeri Batam, 2026)
Network-Attached Storage (NAS) based on low cost Single Board Computers (SBC) offers an affordable alternative to commercial storage systems, yet its exposure to network-based threats requires a robust and layered security approach. This research implements the Defense-in-Depth (DiD) framework on an Orange Pi based NAS running Debian 12, integrating host-based security mechanisms and the ZFS file system to enhance data integrity, availability, and system resilience. The security layers include firewall restrictions, intrusion prevention with Fail2Ban, integrity monitoring using AIDE and rkhunter, system auditing with Lynis, and log analysis with Logwatch. Additionally, ZFS snapshots and the Sanoid retention policy are applied to provide rapid data recovery with minimal storage overhead. Experimental results show that all defense layers function effectively under testing scenarios such as brute-force attempts, unauthorized port access, file modification, and data deletion. ZFS snapshots successfully restore deleted or altered files, ensuring minimal Recovery Point Objective (RPO) of one hour. System performance remained stable, with CPU usage averaging only 7.9% and memory usage at 33%, indicating that the DiD model is feasible even on low-resource SBC hardware. These findings demonstrate that a cost-efficient SBC-based NAS can achieve strong resilience against common cyber threats through layered security design and modern file system capabilities.